2002
DOI: 10.1073/pnas.052693999
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a diterpenoid substance with potent neuroprotective activity from fetal calf serum

Abstract: Excess activation of glutamate receptors and production of free radicals including nitric oxide may result in severe and irreversible damage to the mammalian central nervous system (CNS), but endogenous defense systems that protect neurons from these insults are poorly understood. Here, we purified and isolated a neuroprotective substance, which has been named ''serofendic acid,'' from a lipophilic fraction of FCS based on the ability to protect rat primary cortical neurons against nitric oxide cytotoxicity. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 32 publications
(38 reference statements)
1
49
0
Order By: Relevance
“…We previously reported that the concentration of serofendic acid contained in fetal calf serum was in the order of tens of nM (1). In addition, serofendic acid significantly prevented acute glutamate neurotoxicity at a concentration as low as 1 nM (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that the concentration of serofendic acid contained in fetal calf serum was in the order of tens of nM (1). In addition, serofendic acid significantly prevented acute glutamate neurotoxicity at a concentration as low as 1 nM (3).…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified a neuroprotective substance, serofendic acid, in the ether extract of fetal calf serum based on an ability to protect rat primary cortical neurons from nitric oxide (NO) donor-induced cytotoxicity (1). Serofendic acid was found to be a sulfurcontaining atisane-type diterpenoid (15-hydroxy-17-methylsulfinyl-latisan-19-oic acid) (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serofendic acid is a 15hydroxy17methylsulfinylatisan19 oic acid, a sulfurcontaining atisantype diterpenoid (22). It is a lowmolecularweight (MW 382) compound and exhibits a potent protective effect against neurotoxicity induced by glutamate, NO, and oxidative stress without inhibiting glutamate receptors in cultured cortical, striatal, and spinal cord neurons (23 -26).…”
Section: Serofendic Acid Protects Against Myocardial Ischemia-reperfumentioning
confidence: 99%
“…1), from fetal calf serum and described their potent protective activity in cortical neurons against both nitric oxide donor and glutamate cytotoxicity. 5) These observations prompted us to examine the possible neuroprotective activity of our synthetic compounds that have a variety of bridged skeletons. Here we report that kaurene derivatives act as potential neuroprotective agents.…”
mentioning
confidence: 99%